Model Parameter Identification of Supercapacitors Using Metaheuristic Gradient Based Optimization - Yasin, Ahmad (2023)
A Master of Science thesis in Mechatronics Engineering by Ahmad Hussein Yasin entitled, “Model Parameter Identification of Supercapacitors Using Metaheuristic Gradient Based Optimization”, submitted in November 2023. Thesis advisor is Dr. Rached Dhaouadi and thesis co-advisor Dr. Shayok Mukhopadhyay. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).